Effect of CX3CL1/CX3CR1 gene polymorphisms on the clinical efficacy of carboplatin therapy in Han patients with ovarian cancer - Wang, Xin-Chen; Zhou, Hong; Jiang, Wen-Jing; Jiang, Peng; Sun, Yan-Cai; Ni, Wei-Jian (Frontiers in Genetics, 2023)
Gene polymorphisms have a close relationship with the clinical effects of carboplatin for ovarian cancer. Here, we investigated the relationship between CX3CL1 and CX3CR1 genotypes and the clinical efficacy of carboplatin in ovarian cancer, thereby clarifying the unidentified genetic factors that influence the efficacy of carboplatin in ovarian cancer. Based on the above purposes, we used Sequenom Mass ARRAY technology to detect CX3CL1 and CX3CR1 gene polymorphisms in 127 patients with carboplatin-treated ovarian cancer. We performed various statistical analyses to evaluate the effects of CX3CL1 and CX3CR1 genetic variants, demographic data, and clinical characteristics on the effect of carboplatin therapy. The results show that the CX3CL1 genotypes rs223815 (G>C) and rs682082 (G>A) will significantly affect the clinical efficacy of carboplatin for ovarian cancer (P < 0.05), while the other six genotypes and all CX3CR1 genotypes have no significant effect (P > 0.05). In addition, only one population factor, age, had a significant effect on the clinical efficacy of carboplatin-treated ovarian cancer (P < 0.05). Based on the above research results, we concluded that the clinical efficacy of carboplatin in ovarian cancer patients was significantly correlated with age and CX3CL1 polymorphism factors; however, more in-depth effects and mechanisms need to be explored by large-scale, multicenter studies.